EDUKASI TEKNIK MENYUSUI YANG BENAR PADA IBU NIFAS - Hastuti Husain; Theresia Limbong; Subriah, Subriah; Agustina Ningsi; Maria Sonda (J-ABDI: Jurnal Pengabdian kepada Masyarakat, 2023)
These Community Service Partners are Midwives and Postpartum & Breastfeeding Mothers. The problems are: (1) The coverage of exclusive breastfeeding is still low because many postpartum mothers, especially primiparous mothers, do not have sufficient knowledge about breastfeeding techniques because they have never breastfed/breastfed before. (2) The need for health education regarding good and correct breastfeeding techniques for postpartum mothers. The external target is for postpartum mothers to know and implement correct breastfeeding techniques so that they are able to meet the nutritional needs of their babies and reduce the morbidity rate in babies. The methods used are: lecture, demonstration, discussion, and question and answer. The results achieved are (1) There is an increase in the knowledge of post-partum & breastfeeding mothers at the Kassi-Kassi Makassar Community Health Center regarding correct breastfeeding techniques where the Posttest results are better than the pre-test results, (2) Post-partum mothers can breastfeed their babies well and correctly